ANALISIS PENGARUH MOTIVASI, SOSIALISASI, DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KPP PRATAMA BATAM SELATAN - Sianturi, Reka Delima; Wage, Sunarto (SCIENTIA JOURNAL, 2021)
This study means to decide the analysis of the effect of motivation, socialization, and understanding of taxpayers on taxpayer compliance at KPP Pratama South Batam. The population in this research is 346.894 individual taxpayers, and the sample is determined by using the Slovin formula, which is 400 taxpayers. Samples were taken using simple random sampling technique. The data used is primary data in the form of distributing questionnaires through Google Form with a Likert scale of 1-5 points. The data analysis technique used is instrument test (validity test and reliability test), descriptive analysis, classical assumption test (normality test, multicollinearity test and heteroscedasticity test), multiple linear analysis and hypothesis testing (partial test, simultaneous test and coefficient of determination test). The results of the partial test of tax motivation have no significant effect on taxpayer compliance, while socialization and understanding of taxation have a significant effect on taxpayer compliance. The results of the simultaneous test of motivation, socialization, and understanding of taxation have a significant effect on taxpayer compliance. The results of the determination test obtained a value of 0.257 which means that the motivation, socialization and understanding of taxpayers have an influence of 25.7% on taxpayer compliance and the remaining 74.3% is influenced by other variables.